Magnetic structure of cast glass-coated amorphous microwire with positive magnetostriction - Baranov, Serghei (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
The effect of the residual magnetization in zero magnetic fields in two-domain magnetic